Piil Pesenggiri as Peace Culture: A Local Wisdom Based Resolution of Land Conflicts In Mesuji, Lampung - Syukron, Buyung; Rusmadi, R (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2018)
The presence of big companies holding the certificate of cultivation right on lands or hak guna usaha in Mesuji, Lampung has triggered numerous land conflicts. Various efforts have been made, but in fact, they have not been able to resolve the conflicts. A new approach in resolving the conflicts is, thus, needed. This article, using descriptive-qualitative research method, tries to present a new model of resolution of land conflicts in Mesuji, Lampung Province, based on local wisdom called piil pesenggiri, the philosophical values of Lampung people. Piil pesenggiri itself is a sense of self-esteem; it is principles the Lampung people must follow in order to live in dignity. The article argues that the values contained in piil pesenggiri can be used to resolve the land conflicts in Mesuji since they have been inherent in the life of Lampung society. The values are such as juluk adek (principles of success), nemuin yimah (principles of respect), nengah nyappur (principles of equality), and sakai sambayan (principles of cooperation). All those values are a manifestation of peace culture that can be used as a medium of conflict resolution.